Insight Into Distinct Functional Roles of the Flagellar ATPase Complex for Flagellar Assembly in Salmonella - Minamino, Tohru; Kinoshita, Miki; Namba, Keiichi (Frontiers in Microbiology, 2022)
Most of motile bacteria utilize the flagellar type III secretion system (fT3SS) to construct the flagellum, which is a supramolecular motility machine consisting of basal body rings and an axial structure. Each axial protein is translocated via the fT3SS across the cytoplasmic membrane, diffuses down the central channel of the growing structure and assembles at the distal end. The fT3SS consists of a transmembrane export gate complex and a cytoplasmic ATPase ring complex with a 12 FliH, 6 FliI and 1 FliJ stoichiometry, which is structurally similar to the cytoplasmic part of FOF1-ATPsynthase. The export gate complex requires the FliH12FliI6FliJ1 ring complex to become an active protein transporter. The FliI6 ring has six catalytic sites and hydrolyzes ATP at an interface between FliI subunits. FliJ binds to the center of the FliI6 ring and acts as the central stalk to activate the export gate complex. The FliH dimer binds to the N-terminal domain of each of the six FliI subunits and anchors the FliI6FliJ1 ring to the flagellar base. In addition, FliI also exists as the hetero-trimer with the FliH dimer in the cytoplasm, and the rapid association-dissociation cycle of this hetero-trimer with the docking platform of the export gate complex promotes sequential transfer of export substrates from the cytoplasm to the export gate for high-speed protein transport. In this review article, we will describe the current understanding of multiple roles of the flagellar cytoplasmic ATPase complex for efficient flagellar assembly.